Draft Resolusi Konflik Penyelesaian Konflik Perang Sipil di Libya Tahun 2011 - Bagaskara, Bagaskara (FAI Unismuh Palu, 2019)
Libya as a nation has become a country that affected by the Arab Spring. The impact of the democratic wave that swept all over the country has been one of the reasons of the Libya’s civil war. Qaddafi’s otoritarian regime administration also aggravate the situation and thus increase the want of fundamental democratic system. Libya’s conflict was divided into two sides which were the Qaddafi’s loyalist and the opposition. There were other countries that were involved within the Libya’s civil war and had made the conflict worsen.